Compost application in integrated and organic fruit cultivation - Szabó, Anita; Gonda, István; Vágó, Imre (Acta Agraria Debreceniensis, 2012)
Nowadays the success vegetable and fruit production are unimaginable without regular nutrient management. One of the ways to supply the required nutrients in an environmentally friendly way is the application of composts, which is less widespread so far. Compost doses were applied in biological and integrated apple orchards in cooperation with the Institute of Horticultural Science in the years 2010 and 2011. Different changes were resulted by the compost treatments in the examined parameters in case of both apple varieties (Golden Delicious and Pinova). There is no clear effect of compost on the changes of ash-, total acids, Vitamin C and the sugar content until now, because the improvement of the nutritional indicators takes more time. However significant differences were observed after one year between the apple varieties. Higher ash-, total acids and sugar content were measured in case of the apple variety Pinova, while the measurements showed higher Vitamin C content in case of the variety Golden Delicious.